Paediatric image‐guided radiation therapy: determining and evaluating appropriate kilovoltage planar exposure factors for the Varian on‐board imager. Issue 1 (3rd September 2019) - Ryan, John; Willis, David
Abstract: Introduction: Kilovoltage (kV) orthogonal imaging is commonly used for image‐guided radiation therapy (IGRT) in paediatrics. Paediatrics have an increased sensitivity to radiation. Exposure factors need to be optimised so that imaging dose is kept as low as reasonably achievable (ALARA). Methods: A table of low‐dose IGRT radiographic exposure factors for paediatric IGRT was determined through a phantom study. Four anatomical sites, head and neck, thorax, abdomen and pelvis, were investigated. The table was evaluated against standard manufacturer pre‐sets. Dose was evaluated in terms of system‐reported entrance surface air kerma (ESAK). Qualified participants volunteered to perform offline image matching in a further phantom study, recording misalignments detected and providing subjective assessments of image quality using an electronic survey tool. A statistical comparison of matching accuracy was conducted. Results: Twelve radiation therapists or radiation oncologists completed the image matching task and survey. The low‐dose exposure table reduced imaging dose by 20–94% compared to manufacturer pre‐sets. No significant difference was observed in the accuracy of image matching (head and neck P = 0.82, thorax P = 0.15, abdomen P = 0.33, pelvis P = 0.59). Participant image exposure preference was largely equivocal. Conclusions: Optimising radiographic exposures in paediatric IGRT is feasible, logical and therefore reasonably achievable. Implementation of the low‐dose exposure table presented in this study should be considered by paediatric radiotherapy departments wishing to image gently without compromising the potential to detect set up errors. Further study using a contrast detail phantom and contrast to noise image analysis software is recommended. Abstract : Appropriate image dose optimisation for paediatric image‐guided radiation therapy can r esult in a 20–94% reduction in radiation dose, with no decrease in image matching accuracy.